Strategies in Mastering Science Process Skills in Science Experiments: A Systematic Literature Review - Idris, Nazihah; Talib, Othman; Razali, Fazilah (Jurnal Pendidikan IPA Indonesia, 2022)
Science is a knowledge discipline that is experimentally oriented. The science experiment is one of the core activities in science learning. It is a process that prioritises methods of investigation and problem-solving where the scientific method is employed. In science experiments, mastery of scientific process skills is required. Hence, it is crucial as this will expose students to scientific methods and knowledge. This study aims to identify what are the appropriate strategies that may be employed to augment learners’ science process skills. This article conducts a systematic literature review and twenty-two articles have been chosen to be analysed. The current study combined many research designs, where the review fulfilled the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) publishing standard. Web of Science and Scopus, two well-known databases, were used to discover articles for this study. This review includes a topic based on the thematic analysis which is strategies in mastering science process skills. The results show seven sub-themes based on the topic that are 1) Hands-on and minds-on implementation 2) Inquiry-based approach 3) Discovery learning 4) Strategic manipulative skills 5) Argumentation Skills 6) Using Information and Communication Technologies and 7) Implementing Engineering-oriented science, technology, engineering, and mathematics (STEM) Integration Activities. The research’s findings may motivate science educators to use the appropriate strategies while undergoing science experiments to improve SPS which are important competencies that can influence student’s performance in science learning.